Harakat dan Tanda Baca Mushaf Al-Qur'an Standar Indonesia dalam Perspektif Ilmu Dabt - Madzkur, Zaenal Arifin (SUHUF, 2014)
This paper would like to re-analyze the discussion of the form of vowel and punctuation in the QurÃ¢â‚¬â„¢an of Indonesian Standard that has become the fixed standard for the distribution and publication of the Qur'an in Indonesia since 1984. This study is important, besides as an introduction to the academic text of the study of dabt in the Standard Quran, also as an effort to reinstate the historical development of vowel and punctuation mark in the writing of the QurÃ¢â‚¬â„¢anic discourse (rasm al-mushaf) which are rarely addressed in discussions of the writing of the Qur'an in Indonesia. The shallowness to understand science of dabt often becomes a trigger of the disputes as it is also happened in the discussion of the Ã¢â‚¬Å“Ottoman RasmÃ¢â‚¬Â in the writing of the Qur'an.Keywords: QurÃ¢â‚¬â„¢an of Indonesian Standards, vowel and punctuation marks.